DAMPAK BAGI WANPRESTASI SEBAGAI AKIBAT DARI PERLUASAN MAKNA PERBUATAN MELAWAN HUKUM - Adina Mutiara Tirta; Pranoto Pranoto (Fakultas Hukum Universitas Sebelas Maret, 2026)
This article aims to analyze about the effect of broaden comprehension of tort on breach of contract, hence it aims to give its explanation to public. This study uses doctrinal methods with the nature of prescriptive and applied research. The approach used is the statute approach and conseptual approach using sources in the form of primary and secondary legal materials. While some of legal materials collection technique in this research is by using the method of browsing through the internet media which is then followed by analysis techniques using grammatical and systematic interpretation techniques. The result of this study indicates that broaden of torts’ definition does affect breach of contract, it shows breach of contract is part of torts. It does indicate one who fails to take action of agreement could be considered as a violation of others’ subjective rights and violation of the norms.